2012
DOI: 10.1155/2012/581489
|View full text |Cite
|
Sign up to set email alerts
|

A Case ofBrucellaEndocarditis in Association with Subclavian Artery Thrombosis

Abstract: Brucellosis is a common zoonosis, endemic in Mediterranean countries, and caused by bacteria of Brucella genus. Brucellosis is a systemic infection and the clinical presentation varies widely from asymptomatic and mild to severe disease. Cardiovascular complications are extremely rare. We present a case of arterial thrombosis in a previously healthy young patient with Brucella endocarditis. Careful attention must be paid to any sign or symptom of thrombosis in patients affected by brucellosis, regardless of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 12 publications
0
15
0
1
Order By: Relevance
“…Although this test was rarely done in previous published studies, it seems to have adequate sensitivity (80%). 27,44,45,51,55 The potential diagnostic usefulness of PCR is exemplified by one case with negative blood cultures in which the diagnosis of brucellosis was made from a positive PCR on resected tissue. 27 Despite the fact that brucella is traditionally thought to be a fastidious organism on culture, blood and tissue cultures are sensitive and useful tests for diagnosis of brucella in these cases.…”
Section: Case Presentationmentioning
confidence: 99%
See 3 more Smart Citations
“…Although this test was rarely done in previous published studies, it seems to have adequate sensitivity (80%). 27,44,45,51,55 The potential diagnostic usefulness of PCR is exemplified by one case with negative blood cultures in which the diagnosis of brucellosis was made from a positive PCR on resected tissue. 27 Despite the fact that brucella is traditionally thought to be a fastidious organism on culture, blood and tissue cultures are sensitive and useful tests for diagnosis of brucella in these cases.…”
Section: Case Presentationmentioning
confidence: 99%
“…The mortality rate in published cases is 21%, and many patients’ infection progressed despite adequate therapy. 32,41,50,52,55 A review of published cases suggested that several factors seem to be associated with increased likelihood of mortality with brucella arteritis. Survival seems to be lower in those infected with B suis than in those infected with other strains.…”
Section: Case Presentationmentioning
confidence: 99%
See 2 more Smart Citations
“…Brusella endokarditinde literatürde en sık aortik kapak tutulumu olduğu görülmektedir ve %82'ye varan oranda aortik kapak tutulumu gösterilmiştir ve bizim çalışmamızda bu oran %62,5'tir (19,20). Brusella endokarditinde aortik kapak tutulumu çok sayıda sistemik embolik komplikasyona yol açmaktadır: Süperiyor mezenterik arter anevrizması, miyokardit, splenik apse ve subklavyan arter trombozu gibi pek çok komplikasyon bildirilmiştir (21)(22)(23)(24). Takip ettiğimiz tüm hastalar kapakta vejetasyon ile gelmiş olup, sadece bir hastada periannüler aortik apse de mevcuttu.…”
Section: Discussionunclassified